2007
DOI: 10.1021/om0608253
|View full text |Cite
|
Sign up to set email alerts
|

High-Spin Organocobalt(II) Complexes in a Thioether Coordination Environment

Abstract: A series of electronically and coordinatively unsaturated four-coordinate organocobalt(II) complexes, [PhTt tBu ]Co(R) ([PhTt tBu ] ) phenyltris((tert-butylthio)methyl)borate; R ) Me, Et, Ph, Bn) have been prepared by reaction of [PhTt tBu ]CoCl with the corresponding R 2 Mg reagent. These high-spin, S ) 3/2, complexes have been characterized spectroscopically and several of their structures determined by X-ray diffraction. The R ) allyl derivative, [PhTt tBu ]Co(η 3 -allyl), is low spin. Reaction of [PhTt tBu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…In the solid state, paramagnetic complex 1 has a square-planar geometry, and solution-state magnetic-moment measurements are also consistent with a square-planar low-spin d 7 configuration (m eff = 2.2 m B ). [21,22] The solution-state magnetic moment of complex 1 is quite similar to that of the related square-planar complex [(N(SiMe 2 CH 2 PPh 2 ) 2 )Co(CH 2 SiMe 3 )] (2.…”
mentioning
confidence: 72%
“…In the solid state, paramagnetic complex 1 has a square-planar geometry, and solution-state magnetic-moment measurements are also consistent with a square-planar low-spin d 7 configuration (m eff = 2.2 m B ). [21,22] The solution-state magnetic moment of complex 1 is quite similar to that of the related square-planar complex [(N(SiMe 2 CH 2 PPh 2 ) 2 )Co(CH 2 SiMe 3 )] (2.…”
mentioning
confidence: 72%
“…Carbonylation of [PhTt tBu ]Co(R), R = Me, Et, Ph, results in a rapid color change from green to red signaling formation of low-spin [PhTt tBu ]Co(CO)(C(O)R). Alternatively, [PhTt tBu ]Co(Bn) and [PhTt tBu ]Co(η 3 -allyl) are reduced to the monovalent [PhTt tBu ]Co(CO) 2 by CO. We have further found that this dicarbonyl adduct is in equilibrium with the high-spin monocarbonyl, [PhTt tBu ]Co(CO) [68]. For comparison, CO addition to [Tp tBu ]Co(Me) yielded [Tp tBu ]Co(CO) [64] and the smaller [Tp iPr2 ]Co(R), R = allyl, p -methylbenzyl, converted to [Tp iPr2 ]Co(CO)(C(O)R) [63].…”
Section: Organo-cobalt and Organo-iron Complexesmentioning
confidence: 96%
“…The R = Me and Bn derivatives of Fe and Co were characterized by X-ray diffraction analyses [68,69]; the Bn derivatives feature η 1 -benzyl ligation. The complexes exhibit magnetic moments consistent with high-spin states, S = 3/2 for Co and S = 2 for Fe.…”
Section: Organo-cobalt and Organo-iron Complexesmentioning
confidence: 99%
See 2 more Smart Citations